2019
DOI: 10.3390/su12010240
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Heritage Management Using Remote Sensing Data and GIS Techniques around the Archaeological Area of Ancient Jeddah in Jeddah City, Saudi Arabia

Abstract: Historic Jeddah is located on the eastern shore of the Red Sea. Historic Jeddah was designated as a UNESCO world heritage site in 2014. The new urban development for the city of Jeddah has resulted in different spatial patterns. The southern part of Jeddah city falls within the moderate zone, because this area is well developed in regard to infrastructure with rainstorm and sewage networks. The middle area of the city falls within high vulnerability risk due to its high population, shallow water depth, flat sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…for a deep knowledge of the contexts, essential in the field of archaeological research. The use of Sentinel-2 images could also be included in the practices for the creation of the archaeological risk assessment map to be handed over to the Soprintendenza, for the protection of cultural heritage in the case of urban sprawl and land use change processes [116][117][118][119][120][121].…”
mentioning
confidence: 99%
“…for a deep knowledge of the contexts, essential in the field of archaeological research. The use of Sentinel-2 images could also be included in the practices for the creation of the archaeological risk assessment map to be handed over to the Soprintendenza, for the protection of cultural heritage in the case of urban sprawl and land use change processes [116][117][118][119][120][121].…”
mentioning
confidence: 99%
“…These systems' structuring methodologies are highly debated and continuously advancing topic in scientific research and dedicated tools. This is evidenced by numerous research that has just been concluded or is still in progress [20][21][22][23][24][25][26][27]. The use of GISs for CMPs is increasingly frequent even within the Keeping it Modern initiative of the Getty Foundation.…”
Section: Geographic Information Systems For Cultural Heritage Managementmentioning
confidence: 99%
“…It is also concluded that tourism is the main driver of the digital transformation of heritage [35] and digital technology tools, such as 3D technology, laser technology, geographic information technology, database modelling, providing important tools for risk management, monitoring, planning and visualisation of cultural heritage [36]. In the analysis of the scientific communities that have been found are applications in archaeology, with related means of detection, such as laser scanning, radar, remote sensing or photogrammetry [37].…”
Section: Introductionmentioning
confidence: 99%